Exploring psychological correlates of peers and fathers of drug addict adolescents (Dhaka University Journal of Biological Sciences, 2019)
Drug dependency is clearly a problem for almost every country and Bangladesh is no exception. As the parents and peers are the closest persons of an adolescent whether addict or non-addict, so the present study was conducted with the following objectives: (a) To explore the peer relationship of the drug addict adolescents, (b) to investigate the parenting style of the fathers of the drug users and (c) to find the economic status of adolescent drug users. 60 male drug addict adolescents from different areas of Dhaka city were selected following snow ball technique. For the assessment of peer relation a scale drug and alcohol use-High risk behavior by Church (1994) was translated into Bangla and for assessing parenting style of the fathers of adolescents drug addicts Parental Acceptance/Rejection Questionnaire Child (PARQ), Short version of Rohner (2004b) was translated into Bangla and were used. For the analysis of the obtained data frequency count and percentage of responses made by the drug addict adolescent about their peers and fathers were calculated. The results show that the adolescent drug addict has very close relation with their peer as the type of drugs, frequency of taking drug and even factors determining their being drug addict are almost same. Results further show that parenting style of the fathers of the drug addict adolescent is rejective. Most of the adolescent get coldness or lack of affection, hostility or aggression, indifference or neglect, undifferentiated rejection but little warmth from their fathers. Finally, addiction is found to spread over access all economic status from almost lowest to highest in the present study.Dhaka Univ. J. Biol. Sci. 28(1): 9-20, 2019 (January)